Ancient libraries - Kèonig, Jason; Oikonomopoulou, Aikaterini 1977-; Woolf, Greg (Cambridge Cambridge University Press, 2013)
"The circulation of books was the motor of classical civilization. But books were both expensive and rare, and so libraries - private and public, royal and civic - played key roles in articulating intellectual life. This collection, written by an international team of scholars, presents a fundamental reassessment of how ancient libraries came into being, how they were organized, and how they were used. Drawing on papyrology and archaeology, and on accounts written by those who read and wrote in them, it presents new research on reading cultures, on book collecting, and on the origins of monumental library buildings. Many of the traditional stories told about ancient libraries are challenged. Few were really enormous, none were designed as research centres, and occasional conflagrations do not explain the loss of most ancient texts. But the central place of libraries in Greco-Roman culture emerges more clearly than ever"-- Provided by publisher.
1. Libraries in ancient Egypt / Kim Ryholt -- 2. Reading the libraries of Assyria and Babylonia /Eleanor Robson -- 3. Fragments of a history of ancient libraries / Christian Jacob -- 4. Men and books in fourth-century BC Athens / Massimo Pinto -- 5. From text to text: the impact of the Alexandrian Library on the work of Hellenistic poets / Annette Harder -- 6. Where was the Royal Library of Pergamon? An institution found and lost again / Gaelle Coqueugniot -- 7. Priests, patrons and playwrights: libraries in Rome before 168 BC / Mike Affleck -- 8. Libraries in a Greek working life: Dionysius of Halicarnassus, a case study in Rome / Daniel Hogg -- 9. Libraries and intellectual debate in the Late Republic: the case of the Aristotelian corpus / Fabio Tutrone -- 10. Ashes to ashes? The Library of Alexandria after 48 BC / Myrto Hatzimichali -- 11. The non-Philodemus book collection in the Villa of the Papyri / George W. Houston -- 12. 'Beware of promising your library to anyone': assembling a private library at Rome / T. Keith Dix -- 13. Libraries for the Caesars / Ewen Bowie -- 14. Roman libraries in the city of Rome / Matthew Nicholls -- 15. Flavian libraries in the city of Rome/ Pier Luigi Tucci -- 16. Archives, books and sacred space in Rome / Richard Neudecker -- 17. Visual supplementation and metonymy in the Roman public library / David Petrain -- 18. Libraries and reading culture in the High Empire / William A. Johnson -- 19. Myth and history: Galen and the Alexandrian library / Michael W. Handis -- 20. Libraries and paideia in the Second Sophistic: Galen and Plutarch / Alexei V. Zadorojnyi -- 21. The professional and his books: special libraries in the Roman world / Victor Martâinez and Megan Finn Senseney.
Includes bibliographical references (pages 418-462) and index.
Keywords: Libraries -- History -- To 400.